CRYSTALLIZATION CONDITIONS OF PLAGIOCLASE IN VOLCANIC COMPLEXES OF SULAWESI ISLAND, PACIFIC OCEAN - A.V. Kotlyarov; N.V. Dmitrieva; V.A. Simonov; I.Yu. Safonova; N.S. Karmanov; I.R. Nizametdinov (Минералогия)
Mineralogical and thermobarogeochemical studies allowed us to reveal the crystallization conditions of plagioclase in volcanic complexes of Sulawesi Island (Pacific Ocean). The composition of plagioclase indicates the presence of three types of melts, which were involved in the formation of plagioclase phenocrysts in basalts, andesites and dacites, as well as crystallites in the groundmass of andesites and dacites. The analysis of glasses of heated melt inclusions in plagioclase indicates the involvement of two contrasting melts (mafic and felsic) in crystallization of phenocrysts. At the final stages of the volcanic process, plagioclase in matrix of andesites and dacites formed from another felsic melts with maximum alkali content. The presence of primary syngenetic melt and fluid inclusions in plagioclase phenocrysts indicates the phase separation of felsic magmas, which led to the crystallization of feldspar phenocrysts of different composition during the formation of dacites. Computational modeling in a program of (Putirka, 2008) based on the composition of plagioclases, glasses of heated inclusions and glasses from the groundmass allowed us to estimate the crystallization temperatures of feldspar phenocrysts in basalt (1160–1120 ºС), andesite (930–890 ºС) and dacite (1035–970 ºС), as well as the feldspar microcrystals in the groundmass of andesite (875–810 ºС) and dacite (900–865 ºС).